ANALISIS PENGARUH BELANJA LANGSUNG, PENANAMAN MODAL ASING (PMA), TENAGA KERJA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN/KOTA PROVINSI KALIMANTAN BARAT - B01112022, Sumarni (Jurnal Pembangunan dan Pemerataan, 2016)
The purpose of this research is to know the influence of direct expenses, Foreign Direct Investment (FDI), and manpower toward economics’ growth in Kabupaten/Kota Provinsi Kalimantan Barat in 2009-2013. This research used quantitative approach. It is used secondary data with instrument data likes direct expenses data, foreign direct investment and active manpower. The analytic method that the writer used is double regression analysis with fixed effect model. The resources data get from Badan Pusat Statistik Provinsi Kalimantan Barat. The report of the research shows that the direct expenses’ variabel is have positive effect and significant toward economics’ growth in significancy level around 0.0000 < 0.05. Foreign direct investment is have positive effect and significant toward economic’s growth in significancy level around 0.0004 < 0.05. The manpower also have positive effect but not significant toward economic’s growth in significancy level around 0.8519 < 0.05.Keywords : economic growth , direct spending, foreign direct investment, manpower